1990
DOI: 10.1177/002221949002300907
|View full text |Cite
|
Sign up to set email alerts
|

Persisting Problems of Adults with Learning Disabilities

Abstract: The issue of persistence of learning disabilities into the adult years was investigated. The study examined the self-reported comparisons of problems resulting from learning disabilities during school-age years (retrospectively) and in adult years. The responses of 133 adults categorized as highly successful and moderately successful in employment showed that both groups deteriorated markedly in the areas of functioning typically included in diagnostic and remediation efforts. This established a case for persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…However, they tended to be only as debilitating as the severity of their learning disabilities or the success of their own systems of accommodation. (p. xiv) Gerber et al (1990) investigated the persistence of LD across the span of adult years. A group of 133 adults (81 males and 52 females) ranging in age from 23 to 71 (mean age = 42.1) categorized as moderately successful and highly successful with LD were studied.…”
Section: Journal Of Learning Disabilities 45(1)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, they tended to be only as debilitating as the severity of their learning disabilities or the success of their own systems of accommodation. (p. xiv) Gerber et al (1990) investigated the persistence of LD across the span of adult years. A group of 133 adults (81 males and 52 females) ranging in age from 23 to 71 (mean age = 42.1) categorized as moderately successful and highly successful with LD were studied.…”
Section: Journal Of Learning Disabilities 45(1)mentioning
confidence: 99%
“…However, the authors pointed out that the findings might be a function of the ever-increasing complexities (being developmentally appropriate) of work and daily routines as adulthood unfolded. Moreover, Gerber et al (1990) commented that after the issue of persistence of LD from school to beyond school had been established in the thinking of LD professionals, a new realization became part of the conversation-"that things do not get better over time, and that problems associated with LD can even get worse in the adult years" (p. 572).…”
Section: Journal Of Learning Disabilities 45(1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dyslexia is typically diagnosed in second or third grade (or later), once children have failed to learn to read as expected; therefore, children may be exposed to repeated academic failure before diagnosis (Fletcher et al, 2006; Shaywitz et al, 2007). Children with dyslexia can experience a host of social and emotional problems secondary to reading and associated academic difficulties (Brooks, 2001; Fletcher et al, 2006; Gerber et al, 1990), and both dyslexia and its associated negative outcomes can persist into adulthood (Raskind et al, 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Data from the US National Health Interview Survey demonstrated that LD prevails in 16.8 percent of the sampled population (Boyle, Decoufle, & Yeargin‐Allsopp, ; see also a more recent US sample Altarac & Saroha, ). Most of the LD literature focuses on children, but it has been established that LD affects individuals throughout their life (Gajar, ), and there are cases in which some of its symptoms become worse over time (Gerber et al, ). Thus, LD is relevant to personnel and to organizational psychology because almost one‐fifth of employees may have LD that may influence their performance…”
Section: Introductionmentioning
confidence: 99%